A Novel High-Power Battery-Pseudocapacitor Hybrid Based on Fast Lithium Reactions in Silicon Anode and Titanium Dioxide Cathode Coated on Vertically Aligned Carbon Nanofibers. (1st October 2015) - Klankowski, Steven A.; Pandey, Gaind P.; Malek, Gary A.; Wu, Judy; Rojeski, Ronald A.; Li, Jun
Graphical abstract: Highlights: A unique battery-supercapacitor hybrid has been demonstrated. Both Si anode and TiO2 cathode are fabricated in the form of nanocolumnar shells coated on VACNFs. Hybrid cells achieve stable charge-discharge cycles in the supercapacitor power regime. Abstract: An electrochemical cell representing a battery-supercapacitor hybrid is demonstrated with a Si anode and a TiO2 cathode based on Lithium chemistry. Both materials are fabricated as coaxial shells with an oblique nanocolumnar structure anchored on vertical aligned carbon nanofiber arrays. The Li + ion transport and electrical connection is greatly enhanced with such nanoporous core-shell architectures, leading to optimal Li storage properties. The full theoretical capacity of the shell materials has been obtained at normal C-rates (C/1 to C/2) for Si (∼3, 000 to 3500 mA h g −1 ) and TiO2 (∼170 mA h g −1 ) half-cells, respectively, with excellent cycling stability. More importantly, much higher rates (up to 4.7CSi for Si and 76CTiO2 for TiO2 ) can be applied at relatively small capacity loss, approaching the properties of supercapacitors. The charge-discharge profiles show battery-supercapacitor hybrid features, which are attributed to the short Li + diffusion path across the solid materials and the large pseudocapacitive contribution from fast surface reactions. A full cell containing similar volume of Si and TiO2 shows a high specific energy (103 W h kg −1 ) at low current rates, comparable to a decent battery, and a remarkable specific power (56, 000 W kg −1 ) at high current rates, matching the state-of-the-art supercapacitors.